EVALUATION OF INTERMOLECULAR INTERACTION OF CALCIUM CARBONATE, BARIUM SULPHATE AND IRON (II) SULFIDE SOLID DISSOLUTION IN DTPA AND EDTA (Jurnal Teknologi (Sciences & Engineering), 2025)
In this work, formulations for dissolution of calcium carbonate (CaCO3), barium sulphate (BaSO4) and iron (II) sulphide were developed using chelating agents such as ethylene diamine tetra acetic acid (EDTA) and diethylenetriamine pentaacetate acid (DTPA). Tri potassium EDTA (EDTA-K3), tetrasodium EDTA (EDTA-Na4) and pentapotassium DTPA (DTPA-K5) were blended with synergist chemicals to dissolve CaCO3, FeS and BaSO4 solids, respectively. Synergists used for CaCO3 were hydrochloric acid (HCl) and acetic acid (HAc). The synergist for BaSO4 are potassium carbonate (K2CO3), and FeS is formic acid. Molecular dynamic simulations were conducted to study the intermolecular interaction between oxygen in the chelating agent with the metal ion in the solid scale. The intermolecular interaction (g(r)) of oxygen in EDTA-K3 with Ca shows an increment from 6.06 to 6.86 at a radius (r) of 2.25 Å with the addition of a synergist. However, intermolecular interaction of Ba with oxygen in DTPA-K5 shows reduction with the addition of synergist from 2.68 to 1.40 at r of 3.25 Å. The intermolecular interaction of Fe with oxygen in EDTA-Na4 also shows reduction with the addition of synergist from 10.7 to 10.01 at r 1.75 Å. Overall, the intermolecular interaction of Fe and Ca with respective chelate agents was good, while Ba was weak. Dissolution test was performed with CaCO3, BaSO4 and FeS using the gravimetric method at 60 °C for 24 hours. The most efficient dissolver was validated with ICP-OES for the highest concentration of dissolved metals.